2014
DOI: 10.1155/2014/150628
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Apolipoprotein E Gene Polymorphism and Mild Cognitive Impairment among Different Ethnic Minority Groups in China

Abstract: The association, in different ethnic groups, of apolipoprotein E (apoE) gene polymorphism with mild cognitive impairment (MCI) has been unclear. Few studies have examined the association in Chinese minorities. The current study explores the association between apoE gene polymorphism and MCI in one of the biggest ethnic groups—the Hui—and compares it with the Han. The Minimental State Exam, Activities of Daily Living Scale, and Geriatric Depression Scale were administered to 306 ethnic Hui and 618 ethnic Han pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…We found that ε4 increased the risk of MCI in a dose-dependent manner, which was also in accordance with previous reports in both White and Chinese populations ( Borenstein et al , 2010 ; Boyle et al , 2010 ; Albert et al , 2014 ; Wang et al , 2014 ). In contrast, the APOE ε2 allele appeared to confer cognitive benefits in the White population ( Blacker et al , 2007 ; Bonner-Jackson et al , 2012 ).…”
Section: Discussionsupporting
confidence: 93%
“…We found that ε4 increased the risk of MCI in a dose-dependent manner, which was also in accordance with previous reports in both White and Chinese populations ( Borenstein et al , 2010 ; Boyle et al , 2010 ; Albert et al , 2014 ; Wang et al , 2014 ). In contrast, the APOE ε2 allele appeared to confer cognitive benefits in the White population ( Blacker et al , 2007 ; Bonner-Jackson et al , 2012 ).…”
Section: Discussionsupporting
confidence: 93%
“…The ApoE ε4 allele polymorphism is an independent risk factor for MCI, and cognitive level in ε4 carriers is lower than noncarriers [103]. ApoE ε4 incidence in MCI patients is significantly higher than the normal population [103]. Risk ratio of late-onset AD in ApoE ε4 carriers is approximately three times higher than noncarriers [104].…”
Section: Insulin Resistance and The Apoe ε4 Allelementioning
confidence: 96%
“…ApoE protein, Aβ, and tau protein interact in a specific way, which may be the biological basis for ApoE effect on dementia development [102]. The ApoE ε4 allele polymorphism is an independent risk factor for MCI, and cognitive level in ε4 carriers is lower than noncarriers [103]. ApoE ε4 incidence in MCI patients is significantly higher than the normal population [103].…”
Section: Insulin Resistance and The Apoe ε4 Allelementioning
confidence: 99%
“…Predictive risk factors for MCI in non-Hispanic cohorts were not associated with MCI in Mexican Americans [ 52 ], who were more likely to be possessed the ApoE ε4 allele less frequently [ 52 ]. In addition, ApoE ε4 allele was protective for MCI only in Han Chinese but not in Hui Chinese [ 53 ].…”
Section: Discussionmentioning
confidence: 99%